Господарсько-корисні ознаки корів різних типів конституції - Черненко, Олександр Миколайович; Chernenko, Oleksandr; Chernenko, O. M.; Chernenko, Oleksandr Mikolajovich; Chernenko, O.; Chernenko, Oleksandr M.; Черненко, Олена Іванівна; Chernenko, O.; Chernenko, O. I.; Chernenko, Olena Ivanivna; Милостивий, Роман Васильович; Mylostyvyi, Roman; et al. (Дніпровський ДАЕУ, 2020)
Наведено результати дослідження впливу типів конституції на господарсько-корисні ознаки високопродуктивних корів швіцької породи. Піддослідні тварини були розподілені на три групи за відхиленням 0,67 SD від середнього значення обʼємно-вагового коефіцієнта (ОВК) по досліджуваній групі тварин одного віку в отеленнях. До малообʼємного типу, з величиною ОВК менше 0,46 л/кг, розподілили 16 корів, до середньообʼємного, з ОВК в межах від 0,46 до 0,56 л/кг, відповідно 44 тварини, а до великообʼємного типу з величиною ОВК, що становив 0,57 л/кг і більше, – 19 корів. Оскільки відмінність тварин усіх груп за масою тіла була у межах 3%, як це характерно аналогам, у корів велико- та середньообʼємного типу конституції з розрахунку на кілограм маси їх тіла забезпечується більше співвідношення об’єму грудного відділу, що й характеризується величиною об’ємно-вагового коефіцієнта. Піддослідні корови за основними промірами екстерʼєру характеризуються добрим розвитком. Проте тварини великообʼємного та середньообʼємного типу конституції мали глибші та ширші груди, з більшою площею поперечного перетину грудей за лопатками і за останнім ребром та більший умовний обʼєм грудного відділу. Ділянки шкіри на шиї та останньому ребрі виявились найбільш інформативні щодо визначення особливостей конституції. Тонша шкіра була у корів цих же типів конституції у ділянці шиї на 0,4 за Р > 0,95 та 0,3 см (близько Р > 0,95), а на рівні останнього ребра на 0,3 (близько Р > 0,95) та 0,5 см за Р > 0,95 порівняно з малообʼємним типом конституції. За індексами будови тіла корови всіх типів конституції мали виражений і консолідований молочний тип. Про це свідчить невисоке значення коефіцієнтів мінливості індексів екстерʼєру в межах 2,2–6,9 %. Порівняно з коровами малооб’ємного типу статистично значуща різниця виявлена на користь корів велико- та середньооб’ємного типів конституції за індексом широкогрудості, відповідно на: 1,9% за Р > 0,999 та 1,8% за Р > 0,999 та індексом широкозадості, відповідно на: 2,4 за Р > 0,99 та 1,0% за Р > 0,95. Між поведінкою корів та їх типом конституції звʼязок не виявлений. Установлено, що молочна продуктивність корів залежить від розвитку грудного відділу в цілому та величини обʼємно-вагового коефіцієнта зокрема. Корови велико- та середньообʼємного типу за 305 діб першої лактації мали вищі надої на 1 314 кг за Р > 0,95, вихід молочного жиру – на 41,6 кг за Р > 0,95, а вихід молочного білка – на 40,8 кг за Р > 0,95. Подібна різниця була і за другу лактацію. Presented study results of the influence of constitution types on economically useful traits of highly productive Swiss breed. The experimental animals were divided into three groups according to the standard deviation of 0.67 from the average value of the volume-to-weight coefficient (VWC) for the studied group of same-aged animals at the calving. To the low-volume type with VWC value of less than 0.46 l/kg 16 cows were allocated, to the medium-volume type with VWC of 0.46 to 0.56 l/kg – 44 cows respectively, and to the large-volume type with VWC value, which amounted to 0.57 l/kg or more – 19 cows. Since the difference in animals’ bodyweight of all groups was within 3%, which is a characteristic of matched pairs design, in cows with the constitution of large and medium volume type per kg of their body weight, there was a greater ratio of the thorax which is characterizing volume-to-weight coefficient value. Experimental cows by the main measurements of the exterior were characterized by good development. However, animals of the high and mid-volume type of constitution had deep and wide chests, with a larger chest cross-sectional area behind the shoulder blades and behind the last rib, and a larger conditional volume of the whole thorax. The skin on the neck and the last rib turned out to be the most informative for the definition of the body types features. The cows of those constitution types had thinner skin on the neck by 0.4 (P > 0.95) and 0.3 cm (approximately P > 0.95), and at the level of the last rib by0.3 (approximately P > 0 95) and 0.5 cm (P > 0.95) compared to the low volume type of constitution. According to body indices, cows of all body types had a pronounced and consolidated dairy type. This was evidenced by the low value of the variability coefficient of the exterior indices in the range of 2.2–6.9%. Compared to cows of low volume type, a statistically significant difference was found in favor of cows with the high and medium-volume type of the constitution by chest width index, respectively, by 1.9% (P > 0.999) and 1.8% (P > 0.999) and backside index, respectively: 2,4%(P > 0.99) and 1.0% (P > 0.95). No correlation was found between the cows’ behaviour and their type of constitution. It has been established that cows’ milk productivity depends on the development of the thorax as a whole and the value of the volume-to-weight coefficient in particular. High and medium-volume type cows for 305 days of the first lactation had higher milk yields by 1 314 kg (P > 0.95), milk fat yield – by 41.6 kg (P > 0.95), and milk protein yield – by 40.8 kg (P > 0.95). There was a similar difference for the second lactation.
The economic traits of cows with different types of constitution
Черненко Олександр Миколайович https://orcid.org/0000-0002-8829-3148 Черненко Олена Іванівна https://orcid.org/0000-0002-5951-6576 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: молочна продуктивність.; milk productivity; грудний відділ; thoracic region; проміри екстерʼєру; measurements of the exterior; індекси будови тіла; constitution indices; товщина шкіри; skin thickness